Research on Foreign Air-to-Ground Missiles Development in 2021 - Liu Ying, Ren Chunyan (Hangkong bingqi, 2022)
In this paper, the latest development tendency of typical air-to-ground missiles abroad are summarized. These missiles include: AGM-158(JASSM), Brimstone missile, Spear missile, Kh-59MKM missile, hypersonic air-to-ground missile, and so on. On the basis of the summary, the characteristics of air-to-ground missile, such as long-range penetration capability, system confrontation, cooperative operation capability and low cost technology, are analyzed.